Revision of the Nearctic genus Tritoxa Loew (Diptera: Ulidiidae) - Sinclair, Bradley J.; Macleod, Alyssa M.; Wheeler, Terry A. (Zootaxa, 2021)
The species of the Nearctic genus Tritoxa Loew are revised. Seven species of Tritoxa are recognized, including two new species: T. californica sp. nov. (type locality: near Spring Garden, California), T. cuneata Loew, T. decipiens sp. nov. (type locality: near Smithers, British Columbia), T. flexa (Wiedemann), T. incurva Loew, T. pollinosa Cole and T. ra Harriot. One species from California and Nevada based on female specimens remains undescribed. A key to all species is provided, species are illustrated and their distributions mapped. Wing patterns may be used to differentiate among all species, although confident identification of certain sympatric species requires confirmation by examination of male genitalia.